Comparative study between medical and surgical management for anal fissure in a rural tertiary care hospital in Karnataka, India - M B Satish Kumar; K Avadhani Geetha; K Sachin (Global Journal of Medicine and Public Health, 2024)
Background Medical and surgical treatment options are both widely practiced for the management of anal fissure, however the debate over which treatment option is superior remains unanswered. Thus, this study was conducted to assess the efficacy and adverse effects of medical and surgical management in the treatment of anal fissure.